2014
DOI: 10.1007/s10067-014-2681-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of coronary artery disease in patients with systemic sclerosis: a systematic review and meta-analysis

Abstract: Several chronic inflammatory disorders, such as rheumatoid arthritis and systemic lupus erythematosus, have been shown to increase coronary artery disease (CAD) risk but the data on systemic sclerosis (SSc) is unclear. We conducted a systematic review and meta-analysis of observational studies that reported odds ratio, relative risk, hazard ratio, or standardized incidence ratio comparing CAD risk in patients with SSc versus non-SSc participants. Pooled risk ratio and 95 % confidence intervals were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Subsequent epidemiological studies and a meta-analysis have confirmed this association with an overall 82% excess risk compared with sex and agedmatch controls [14][15][16].…”
Section: Introductionmentioning
confidence: 51%
“…Subsequent epidemiological studies and a meta-analysis have confirmed this association with an overall 82% excess risk compared with sex and agedmatch controls [14][15][16].…”
Section: Introductionmentioning
confidence: 51%
“…There are some studies investigating the association between SSc, coronary fibrosis, and atherosclerosis. [18][19][20] Microvascular dysfunction and fibrosis has a major role in the pathogenesis of the SSc, especially in cardiac complications. 2,3 Myocardial fibrosis is characteristic for heart involvement in SSc and observed in 50% to 70% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SSc-associated pulmonary involvement, either interstitial lung disease (ILD) or pulmonary arterial hypertension (PAH), has recently emerged as the leading cause of SSc mortality [31]. Furthermore, the occurrence of a high rate of cardiovascular events in SSc patients has been identified suggesting evidence of both large vessel and small vessel vasculopathy [3235]. Despite substantial advances in the overall treatment of SSc and the notable increase in SSc survival accomplished recently, currently, there are no approved disease-modifying therapeutic interventions for SSc and there are no drugs that have been shown to reverse SSc-associated ILD.…”
Section: Introductionmentioning
confidence: 99%